Dinamika Ketersediaan Pangan dan Alih Fungsi Lahan Pertanian Kota Malang - Dita Atasa; Dona Wahyuning Laily; Prasmita Dian Wijayanti (Kadiri University, 2022)
The phenomenon of agricultural land conversion always experiences an increasing trend each year. Consequently, as the main factor in food production, land conversion affects regional food availability. This study aims to determine the availability of food, the composition of food diversity, the dynamics of the agricultural land conversion, and its relationship with food availability in Malang. The secondary data regarding agriculture and demographics from related institutions from the year 2018 to 2020 were employed in the study. The analysis included the Food Balance Sheet (FBS), Food Dietary Patterns (FDP), and Pearson correlation. The results showed that there was a decrease in energy availability from 2018-2020, the value was 2,667 kcal/capita/day, 2,195 kcal/capita/day, and 2,174 kcal/capita/day. Meanwhile, the availability of protein fluctuated, as there was a decrease from 71.22 g/capita/day in 2018 to 53.29 g/capita/day in 2019, then increased to 62.25 in 2020. The quality of food availability was based on the composition of the diversity of food groups from 2018 to 2020, which had not been diverse. The PPH score was less than 100, which had not reached the ideal score, respectively of 77.9; 69.67; and 88.26. Furthermore, each year there was an increase in the agricultural land conversion area to the non-agricultural sector, with an average of 33.5 ha. However, the results of the Pearson correlation stated that the area of agricultural land and energy availability did not have a significant correlation. These results were suspected due to the majority of food availability of Malang originating from the outside regions. Fenomena alih fungsi lahan pertanian selalu mengalami tren peningkatan setiap tahunnya. Padahal, lahan menjadi faktor utama dalam produksi pangan yang berpengaruh pada ketersediaan pangan suatu wilayah. Penelitian ini bertujuan untuk mengetahui ketersediaan pangan, komposisi keragaman pangan, dinamika alih fungsi lahan pertanian dan hubungannya dengan ketersediaan pangan Kota Malang. Data yang digunakanan adalah data sekunder berasal tahun 2018-2020 berasal dari instansi pertanian dan kependudukan. Analisis yang digunakan merupakan Neraca Bahan Makanan (NBM), Pola Pangan Harapan (PPH) dan pearson correlation. Hasil diperoleh bahwa terjadi penurunan ketersediaan energi dari tahun 2018-2020, nilai tersebut adalah 2.667 kkal/kapita/hari, 2.195 kkal/kapita/hari, 2.174 kkal/kapita/hari. Sedangkan ketersediaan protein berfluktuatif, terjadi penurunan dari 71,22 gr/kapita/hari tahun 2018 menjadi 53,29 gr/kapita/hari tahun 2019, selanjutnya mengalami kenaikan menjadi 62,25 pada tahun 2020. Kualitas ketersediaan pangan berdasarkan komposisi keragaman kelompok pangan dari tahun 2018-2020 belum beragam. Hal ini dapat diketahui berdasarkan hasil yang didapat skor PPH < 100 belum mencapai skor ideal, dengan skor masing-masing sebesar 77,9; 69,67; dan 88,26. Selanjutnya, setiap tahunnya terjadi peningkatan alih fungsi lahan pertanian ke sektor non pertanian, dengan rata-rata sebesar 33,5 ha. Sedangkan, hasil pearson correlation menyatakan luas lahan pertanian dan ketersediaan energi tidak memiliki korelasi yang signinifikan. Hasil tersebut diduga karena ketersediaan pangan mayoritas berasal dari bahan pangan yang berasal dari luar Kota Malang.